ҚАРАҚАЛПАҚ ХАЛЫҚ ЕРТЕКЛЕРИ ТИЛИНДЕГИ ЖӘМИЙЕТЛИК – СИЯСИЙ ТАРИЙХЫЙ СӨЗЛЕР - Кунназарова, Ш.М. (SCIENCE and SOCIETY, 2017)
The article deals with outdated words used in folk tales. There are given lexemes from outdated words concerning socio-political life,features of their usage on the material of concrete examples.
Keywords: outdated words; historical words; socio-political life; social-class distinctions; rank; level; profession; social system; management activity